Ancient Indian Politics and its Political Institutionalism: Reminiscence the Arthasastra Tradition of Kautilya - Chakraborty, Tirthankar (Indian Journal of Political Science)
The search for just and ideal policy - one of the basic themes which constantly hunt many of our minds since the ancient times. In fact it is vividly reflected in the discourses and different treatises of ancient Hindu scriptures. Kautilya's Arthashastra was part of it. Both in the popular and intellectual discourses, the idea of 'dharma', the idea of powerful kingship and of its different organs as integral part of the state were posited and were partly incorporated in the administrative machinery, which again followed legal codification and customary inscriptive laws in the dispensation of justice and in governance. This paper is going to highlights the role of political institutionalism in the words of Arthasastra tradition of Kautilya. - Reproduced
Keywords: Hindu Political Thought, Dharma, Kautilya's Arthashastra, Kingship, Danda Niti